Antitumor Features of Vegetal Protein-Based Nanotherapeutics - Silvia Voci; Agnese Gagliardi; Massimo Fresta; Donato Cosco (MDPI AG, 2020)
The introduction of nanotechnology into pharmaceutical application revolutionized the administration of antitumor drugs through the modulation of their accumulation in specific organs/body compartments, a decrease in their side-effects and their controlled release from innovative systems. The use of plant-derived proteins as innovative, safe and renewable raw materials to be used for the development of polymeric nanoparticles unlocked a new scenario in the drug delivery field. In particular, the reduced size of the colloidal systems combined with the peculiar properties of non-immunogenic polymers favored the characterization and evaluation of the pharmacological activity of the novel nanoformulations. The aim of this review is to describe the physico-chemical properties of nanoparticles composed of vegetal proteins used to retain and deliver anticancer drugs, together with the most important preparation methods and the pharmacological features of these potential nanomedicines.